Massage Therapy on Blood Pressure, Anxiety, Pain, and Cholesterol Levels in Hypertensive Patients - Wijayanto, Tri; Sahroni, Mizan; Puspa, Egita Windrianatama (Jurnal Ilmiah Kesehatan (JIKA), 2025)
Hypertension is one of the leading causes of mortality worldwide and can be managed through pharmacological and non-pharmacological approaches, including massage therapy. This study aimed to examine the effects of massage therapy on blood pressure, pain, anxiety, and cholesterol levels in patients with hypertension. A quasi-experimental design with a pretest–posttest control group approach was used. The sample consisted of 22 hypertensive patients divided into intervention and control groups. Blood pressure, pain, anxiety, and cholesterol levels were measured before the first intervention and after the second intervention. Within-group differences were analyzed using paired t-tests, while between-group comparisons were conducted using independent t-test with a significance level of p-value< 0,05. The results showed that massage therapy significantly reduced blood pressure in the intervention group. Systolic blood pressure decreased from 161,81 ± 13,28 mmHg to 143,63 ± 12.06 mmHg (p-value = 0,004), and diastolic blood pressure decreased from 97,27 ± 9,04 mmHg to 85,00 ± 5,91 mmHg (p-value < 0,001). Pain and anxiety scores also decreased significantly, from 7,09 ± 1,00 to 2,18 ± 0,40 (p-value < 0,001) and from 29,82 ± 3,00 to 22,45 ± 3,90 (p-value = 0,03), respectively, and were lower than those in the control group at posttest. Although cholesterol levels increased significantly within the intervention group, no significant difference was found compared to the control group. In conclusion, massage therapy effectively reduces blood pressure, pain, and anxiety in hypertensive patients but does not significantly affect cholesterol levels.